2020
DOI: 10.1021/acs.jafc.0c04376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pyraclostrobin as an Ingredient for Soybean Seed Treatment by Analyzing its Accumulation–Dissipation Kinetics, Plant-Growth Activation, and Protection Against Phytophthora sojae

Abstract: Seed treatment with fungicides has been regarded as a principal, effective, and economic technique for soybean [ Glycine max (L.) Merr.] against pathogenic microorganisms during seed germination and seedling growth. Investigation of the characteristics of seed-treatment reagents is an indispensable basis for their application. The aim of the present work is to evaluate the use of pyraclostrobin as an ingredient for soybean seed treatment by investigating its accumulation−dissipation kinetics in plants, plant-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In a different study, soybean treated with pyraclostrobin was calculated to have a control efficacy of 60.7% (Li et al., 2020). Seedlings treated with pyraclostrobin appeared to have some protection against P. sojae , but disease symptoms were evident and root/leaf malformation were noted (Li et al., 2020). The disease symptoms described in the literature with other fungicide seed treatments were not detected in any of the seed treatments with oxathiapiprolin tested in this manuscript.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a different study, soybean treated with pyraclostrobin was calculated to have a control efficacy of 60.7% (Li et al., 2020). Seedlings treated with pyraclostrobin appeared to have some protection against P. sojae , but disease symptoms were evident and root/leaf malformation were noted (Li et al., 2020). The disease symptoms described in the literature with other fungicide seed treatments were not detected in any of the seed treatments with oxathiapiprolin tested in this manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…Seed treatments with azoxystrobin, trifloxystrobin, and pyraclostrobin did not show significant control of reducing P. sojae (Ellis et al., 2008). In a different study, soybean treated with pyraclostrobin was calculated to have a control efficacy of 60.7% (Li et al., 2020). Seedlings treated with pyraclostrobin appeared to have some protection against P. sojae , but disease symptoms were evident and root/leaf malformation were noted (Li et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on leather root rot of Fragaria ananassa Duchesna caused by Phytophthora cactorum (Libert and Cohn) J. Schr€ ot showed that pyraclostrobin provided excelling control (Rebollar-Alviter and Ellis, 2005). Another experiment on managing P. sojae on soybean using pyraclostrobin as seed treatment showed efficacy for increased chlorophyll level, shoot and root length, root activity, and continuous positive effect on enhancing the plant defense (Li et al, 2020). In contrast, some studies showed decreased sensitivity of P. capsici causing Phytophthora blight in pepper against quinone-outside inhibitor (QoI) fungicides including pyraclostrobin (Ma et al, 2018), suggesting the necessity of using fungicides in rotation to save crops from increased resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Once applied, however, pesticides would enter the surrounding environment through pesticide drift, surface water ow, and soil deposition (Druart et al, 2011). Pyraclostrobin, a strobilurin fungicide, has been applied to a wide range of crops due to its high activity against fungi (Li et al, 2018c)and its unique function to improve crop growth characteristics (Li et al, 2020). Consequently, it has been frequently detected in water bodies and sediments adjacent to highly agricultural areas.…”
Section: Introductionmentioning
confidence: 99%